2017
DOI: 10.1080/13557858.2017.1315365
|View full text |Cite
|
Sign up to set email alerts
|

Does acculturation affect the dietary intakes and body weight status of children of immigrants in the U.S. and other developed countries? A systematic review

Abstract: This study suggests children of immigrants with different cultural backgrounds may interact with host countries to varying degrees, ultimately influencing their diet behaviours and body weight status. Researchers are encouraged to adopt standardized acculturation scales to compare the results across countries and populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
0
16
1
1
Order By: Relevance
“…This influencing factor is supported by the literature, which highlights the impact of acculturation on dietary change. For example, a recent systematic review of the relationship between acculturation, dietary intakes, and the body weight status of children of immigrants concluded that a wide variation exists in the relationship between acculturation and dietary intake 81 . Although this position is supported in our findings, it does not suggest that the positive impact of acculturation was equal to the negative impact.…”
Section: Discussioncontrasting
confidence: 74%
“…This influencing factor is supported by the literature, which highlights the impact of acculturation on dietary change. For example, a recent systematic review of the relationship between acculturation, dietary intakes, and the body weight status of children of immigrants concluded that a wide variation exists in the relationship between acculturation and dietary intake 81 . Although this position is supported in our findings, it does not suggest that the positive impact of acculturation was equal to the negative impact.…”
Section: Discussioncontrasting
confidence: 74%
“…Acculturation has long been thought to influence obesity in immigrant populations since a classic study by Popkin and Udry (1998) provided evidence that immigrants’ obesity rates increased by the number of generations they lived in the United States. Currently, conflicting results on acculturation and obesity were found in adult studies (Ro & Bostean, 2015; Salinas, Abdelbary, Rentfro, Fisher-Hoch, & McCormick, 2014) and child studies (McLeod, Buscemi, & Bohnert, 2016; Zhang, Liu, Diggs, Wang, & Ling, 2019). Recent evidence indicates that the advantage foreign-born Mexican American children had over their U.S.-born counterparts in the 1990s has now diminished so that both foreign-born and U.S.-born Mexican American children have similar rates of overweight/obesity (Maldonado & Albrecht, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Public health and food-related scholarship has paid a great deal of attention to understanding how the predominant food environment of the host country impacts the health of newcomers. These studies largely focus on the impact of dietary acculturation on health outcomes of immigrants (Zhang et al 2019). The health and living conditions of immigrants who work on farms, in processing plants, and in the food service industry have also been subjects of many inquiries that illuminate how labor regulations-or the lack thereof-impact some of the most marginalized, yet crucial, actors in the food system (Moyce and Schenker 2018;Mucci et al 2019).…”
Section: Food Enterprises and Community Revitalizationmentioning
confidence: 99%